Urban Afforestation in Brazil: a Reflection of Environmental Injustice - Taise Ernestina Prestes Nogueira Duarte; Fabio Angeoletto; Enrique Richard; Marcelo Caetano Vacchiano; Deleon da Silva Leandro; João Fernando Copetti Bohrer; Leandro Bernardo Leite; Jeater Waldemar Maciel Corrêa Santos (Terr@ Plural, 2017)
The objective of this paper is to draw broad view of the urban afforestation in Brazil, since the data of the trees around the households from of the Census 2010, made available by IBGE. We try to analyze the dynamics involved in this scenario. These data become very important to help understand the current reality of urban trees in different regions of the country and from these, open doors to new initiatives with the challenge of improving the quality of the urban environment and the environmental services involved. Our data analysis has revealed a positive relationship between urban planning and urban trees. In addition, we’ve found that smaller cities had a higher percentage of trees compared to large and medium cities.